2010
DOI: 10.1007/s00277-010-1034-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of H63D, S65C, and C282Y hereditary hemochromatosis gene variants in Madeira Island (Portugal)

Abstract: Hereditary HFE Hemochromatosis is an inherited disorder of iron metabolism that result from mutations in the HFE gene. Almost all patients with Hereditary Hemochromatosis show a C282Y mutation in homozygosity or in compound heterozygosity with H63D. Also, the mutation S65C has been shown to be associated to a milder iron overload. Since allele and genotype frequencies of these three variants of the HFE gene vary between populations, the determination of their prevalence in Madeira Island will clarify the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…These data suggest that the prevalence of FV Leiden and FII G20210A, associated with thrombophilic events, is lower in Brazilian blood donors than that reported in previous studies concerning blood donors of other countries [ 38 – 40 ]. For HFE mutations (C282Y, H63D and S65C), associated with an iron overload in homozygous or compound genotypes characteristic of HH, we observed a higher frequency (20.3% heterozygous and 1.6% homozygous) of H63D, consistent with previous studies reported internationally [ 21 ] and in a Brazilian population of blood donors from São Paulo [ 41 ]. We did not observe the presence of a homozygous genotype for either C282Y or S65C among the studied population, and the heterozygous compound genotype C282Y/H63D was observed in only one sample.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data suggest that the prevalence of FV Leiden and FII G20210A, associated with thrombophilic events, is lower in Brazilian blood donors than that reported in previous studies concerning blood donors of other countries [ 38 – 40 ]. For HFE mutations (C282Y, H63D and S65C), associated with an iron overload in homozygous or compound genotypes characteristic of HH, we observed a higher frequency (20.3% heterozygous and 1.6% homozygous) of H63D, consistent with previous studies reported internationally [ 21 ] and in a Brazilian population of blood donors from São Paulo [ 41 ]. We did not observe the presence of a homozygous genotype for either C282Y or S65C among the studied population, and the heterozygous compound genotype C282Y/H63D was observed in only one sample.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, patients with HH might benefit from frequent blood donation [ 18 , 19 ]. The most common genetic variants associated with HH are C282Y (rs1800562), H63D (rs1799945) and S65C (rs1800730) [ 20 , 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…In general, the frequency of c.845A [p.282Tyr] in Europe shows a decreasing north-south cline, with values ranging from 5 to 10% in north Europe, and from 1 to 5% in central and south Europe [ 33 ]. The frequency of the c.845A mutation in São Miguel was similar to the one reported in north/central mainland Portugal [ 28 ], but significantly higher than in the Azores Terceira Island [ 27 ], south mainland Portugal [ 28 ], and Madeira Island [ 34 ]. This data validates previous results where mainland Portuguese, especially from north/center, were the main contributors to the Azorean settlement.…”
Section: Discussionsupporting
confidence: 78%
“…Three HFE mutations have now been identified: C282Y, H63D and S65C. [9][10][11] C282Y, a G-to-A transition at nucleotide 845 (G845A) in exon 4 of the HFE gene, results in a cysteine-to-tyrosine substitution at position 282. H63D is a C-to-G transition at nucleotide 187 (C187G) in exon 2, causing a histidineto-aspartic acid substitution at amino acid 63.…”
Section: Introductionmentioning
confidence: 99%